Antiarthritic and Anti-Inflammatory Properties of Cannabis sativa Essential Oil in an Animal Model - Hamid Kabdy; Hajar Azraida; Fatimzahra Agouram; Sara Oufquir; Jawad Laadraoui; Abdelmounaim Baslam; Abdelfatah Aitbaba; Meryem El Ouazzani; Loubna Elyazouli; Rachida Aboufatima; Stefania Garzoli; Abderrahman Chait (MDPI AG, 2023)
Arthritis and inflammatory conditions require effective therapies, but conventional drugs have side effects. This study explored Cannabis sativa L. essential oil (CSEO) as a safer alternative. A chemical characterization of EO conducted via GC/MS showed the presence of sesquiterpene hydrocarbons (67.63%), oxygenated sesquiterpenes (25.91%), and oxygenated monoterpenes (0.99%). The study used three established inflammation induction tests: xylene-induced ear swelling, carrageenan-induced paw inflammation, and inflammation in the paw induced by Freund's complete adjuvant (CFA). Xylene triggered acute inflammation in the ear, while carrageenan-induced acute inflammatory responses through edema and immune-cell recruitment in the paw. CFA-induced arthritis simulated chronic inflammatory conditions. The obtained results demonstrated that treatment with CSEO significantly reduced ear weight in the xylene-induced ear-swelling test, indicating potential inhibition of neutrophil accumulation. In the carrageenan-induced paw inflammation test, CSEO reduced paw volume, suggesting interference with edema formation and leukocyte migration. In the CFA-induced paw inflammation test, CSEO decreased contralateral paw volume, restored body weight, and reduced C-reactive protein levels. Conclusion: this study provides compelling evidence supporting the antiarthritic and anti-inflammatory effects of CSEO. The findings indicate the therapeutic value of EO in the management of arthritis and inflammatory diseases while highlighting the need for further in-depth research to study the molecular mechanisms and validate their safety and efficacy for clinical applications. Preliminary data from this study suggests encouraging prospects for advancing the treatment and prevention of inflammation.